Permasalahan dalam Penyelenggaraan Pendidikan Inklusi di SDN Pinang 7 - Nurfadhillah, Septy; Setyorini, Aprilia; Cempaka, Bunga; Azhar, Cantika Rofiqoh; Fauziah, Putri; Jamirullah, Raihan Fadhlurrahman; Ramadhanty, Salma; Kusminarti, Shanti (ALSYS, 2022)
The implementation of inclusive education in Indonesia aims to provide educational facilities and services for children with special needs (ABK). The implementation of inclusive education has been implemented in elementary schools throughout Indonesia, especially big cities, but in its implementation found many problems. This study aims to describe the problems in the implementation of inclusive education at SDN Pinang 7. Special (GPK) SDN Pinang 7 Tangerang City. The method used is descriptive qualitative which aims to describe "what is" about a variable, symptom or situation. Data collection techniques in this study in the form of interviews, documentation, and observation. The results showed that there were various problems encountered related to the components of educators, students, school management, curriculum, learning processes, cooperation and lack of infrastructure that supports the implementation of inclusive schools, and the incompatibility of infrastructure facilities owned by schools with the needs of children with special needs. In addition, these problems also arise due to the lack of cooperation from various parties, for example with the government and parents and guardians of students.